The Chinese Empire - Terzi, Marinella (Chicago : Childrens Press, 1992)
Discusses the culture of China over a period of four thousand years and examines some of the structures and artwork that remain from that civilization.
Includes index.
Translation of: El Imperio Chino.
School Library Journal.
6.9
5-8
Keywords: China -- History -- Juvenile literature; China -- Antiquities; China -- Civilization; China -- Antiquities; China -- Civilization